Fuzzification of the Saaty’s scale and a presentation of the hybrid fuzzy AHP-TOPSIS model: an example of the selection of a brigade artillery group firing position in a defensive operation - Pamučar, Dragan S.; Božanić, Darko I.; Kurtov, Dejan V. (Vojnotehnički glasnik / Military Technical Courier, 2016)
This paper presents the new way of fuzzification of the Saaty’s scale. In this model of fuzzification, the confidence interval of fuzzy numbers that describes the comparison in pairs’ degree is not determined before the comparison. It is defined (calculated) during and after the comparison, based on the degree of certainty of decision-makers/experts. Thus, the confidence interval can vary depending on the comparison, no matter if it refers to the same degree of comparison. Also, in group deciding, confidence intervals differ depending on the decision-maker/expert’s opinion. Such explanation is supported by the new fuzzyficated Saaty’s scale. The application of the new scale is shown in the hybrid fuzzy AHP-TOPSIS model when choosing firing positions of an artillery brigade group in a defensive operation. Finally, the impact of the degree of certainty on the final decision is analyzed, where it is demonstrated that this element affects output results. The impact is reflected in the change of the size of weight vectors, i.e. output results (the distance from the ideal alternative), as well as in the change of the rank of alternatives, but only at limit values.